Analysis of pre-competitive and competitive anxiety in youth judoka - Interdonato, Giovanna Carla; Miarka, Bianca; Franchini, Emerson (Revista de Artes Marciales Asiáticas, 2013)
Aim: The present study aimed to verify levels of trait anxiety in juvenile judo athletes (between 14 and 18 yrs.) in pre-competitive and competitive moments. Method: Therefore, 40 athletes (20 boys and 20 girls) with 5 ± 2 yrs. of judo practice were analyzed. The instrument used was the "Sport Competition Anxiety Test” (SCAT). In statistical analysis, we observed differences with Friedman and Mann-Whitney tests, p ≤ 0.05. The Spearman correlation coefficient was used to identify the relationship between variables. Results: Results demonstrated that males and females presented higher anxiety in championship, when compared with the training period. When compared gender in interaction with the moment, the competitive female group demonstrated higher anxiety than other groups. A significant and negatives correlations between anxiety, during championship and pre-competitive moments, and judo practice time were found. Conclusions: These data suggest preparatory work during the championship day should be different for male and female athletes, while female athletes have to control anxiety, in the male group other aspects could be analyzed/considered in the preparation of the athlete.